Advances in Virus-Directed Therapeutics against Epstein-Barr Virus-Associated Malignancies. (5th March 2012) - Ghosh, Sajal K.; Perrine, Susan P.; Faller, Douglas V.
Abstract : Epstein-Barr virus (EBV) is the causal agent in the etiology of Burkitt's lymphoma and nasopharyngeal carcinoma and is also associated with multiple human malignancies, including Hodgkin's and non-Hodgkin's lymphoma, and posttransplantation lymphoproliferative disease, as well as sporadic cancers of other tissues. A causal relationship of EBV to these latter malignancies remains controversial, although the episomic EBV genome in most of these cancers is clonal, suggesting infection very early in the development of the tumor and a possible role for EBV in the genesis of these diseases. Furthermore, the prognosis of these tumors is invariably poor when EBV is present, compared to their EBV-negative counterparts. The physical presence of EBV in these tumors represents a potential "tumor-specific" target for therapeutic approaches. While treatment options for other types of herpesvirus infections have evolved and improved over the last two decades, however, therapies directed at EBV have lagged. A major constraint to pharmacological intervention is the shift from lytic infection to a latent pattern of gene expression, which persists in those tumors associated with the virus. In this paper we provide a brief account of new virus-targeted therapeutic approaches against EBV-associated malignancies.